2011
DOI: 10.4085/1062-6050-46.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Hip-Abductor Fatigue and Single-Leg Landing Mechanics in Women Athletes

Abstract: Context: Reduced hip-abductor strength and muscle activation may be associated with altered lower extremity mechanics, which are thought to increase the risk for anterior cruciate ligament injury. However, experimental evidence supporting this relationship is limited. Objective: To examine the changes in single-leg landing mechanics and gluteus medius recruitment that occur after a hip-abductor fatigue protocol. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 61 publications
(77 reference statements)
4
66
2
Order By: Relevance
“…Kernozek et al also found that male subjects effectively reduced the magnitude of the anterior knee shear force by the means of a greater peak knee flexion angles postfatigue during a DL task, which partially supports our findings [32]. Apart from the above two results, the participants had approximately the same hip and knee flexion angle at initial contact during a single-leg DL task following a hip abductor fatigue protocol in Patrek et al's study [33], which indicated that the role of hip abductor activation in protecting the knee during landing needed to be further justified. In addition, fatigue level was divided into five grades, namely, prefatigue, 25% fatigue, 50% fatigue, 75% fatigue, and 100% fatigue, in Mclean and Samorezov's study [22].…”
Section: Discussionsupporting
confidence: 88%
“…Kernozek et al also found that male subjects effectively reduced the magnitude of the anterior knee shear force by the means of a greater peak knee flexion angles postfatigue during a DL task, which partially supports our findings [32]. Apart from the above two results, the participants had approximately the same hip and knee flexion angle at initial contact during a single-leg DL task following a hip abductor fatigue protocol in Patrek et al's study [33], which indicated that the role of hip abductor activation in protecting the knee during landing needed to be further justified. In addition, fatigue level was divided into five grades, namely, prefatigue, 25% fatigue, 50% fatigue, 75% fatigue, and 100% fatigue, in Mclean and Samorezov's study [22].…”
Section: Discussionsupporting
confidence: 88%
“…Activation of the hip abductors can generate an internal hip abduction moment to decrease the medial displacement of the knee and knee abduction angle. Investigators have studied the relationships between the hip abductor strength, hip abductor activation, and knee abduction angle during landing and squatting tasks (Homan et al, 2013;Jacobs and Mattacola, 2005;Jacobs et al, 2007;Patrek et al, 2011;Russell et al, 2006;Wallace et al, 2008;Zeller et al, 2003), but limited intervention strategies are available to train the hip abductors during jump-landing. Several investigators have described hip abductor activation during functional tasks (Boudreau et al, 2009;Distefano et al, 2009;Dwyer et al, 2010), however, muscles demonstrate specificity between training and testing tasks for strength gains (Hortobagyi et al, 1996;Rutherford and Jones, 1986;Wilson et al, 1996).…”
Section: Introductionmentioning
confidence: 98%
“…Weakness and/or insufficient activation of these muscles in females may also contribute to the greater incidence of non-contact ACL injury in females. Some studies have found an association between reduced hip abduction and external rotation strength and increased knee valgus motion during landing (Jacobs, Uhl, Mattacola, Shapiro, & Rayens, 2007;Wallace et al, 2008), however other studies have contradicted these findings (Bolgla, Malone, Umberger, & Uhl, 2008;Lawrence, Kernozek, Miller, Torry, & Reuteman, 2008;Patrek, Kernozek, Willson, Wright, & Doberstein, 2011). The reason for the discrepancy between these studies may, in part, be due to a lack of association between the muscle force produced during a dynamic task and strength during isometric or isokinetic tests, since other factors will also influence muscle force during a dynamic task.…”
mentioning
confidence: 94%